Penetapan Kadar Triprolidina Hidroklorida dan Pseudoefedrina Hidroklorida Dalam Sediaan Sirup Obat Influenza Secara Kromatografi Lapis Tipis Densitometri - Hayun, Hayun; Leswara, Nelly D.; Masrijal, Camelia D.P. (Majalah Ilmu Kefarmasian, 2007)
The determination of pseudoephedrine hydrochloride and triprolidine hydro-chloride in influenza syrup medicine has been performed using TLC densitometric method. Pseudoephedrine hydrochloride and triprolidine hydrochloride were extracted using chloroform at pH 12 from the syrup, and separated using HPTLC silica Kie-selguhr glass plates 60 F 254, 20x10 cm2 as stationary phase, and a mixture of methanol, ammonia and chloroform (40:2:30) as mobile phase. The plates were ana-lyzed using Camag TLC Scanner 3 with UV-detector at 257 nm for pseudoephe-drine hydrochloride and at 290 nm for triprolidine hydrochloride. The results showed that the linearity, limit of detection, and limit of quantitation of the method for pseudoephedrine hydrochloride were 0.9999, 0.0064 µg, and 0.2124 µg respectively; while for triprolidine hydrochloride were 0.9999, 0.0076 µg, and 0.0254 µg respec-tively. The coefficient of variance (CV) of repeatability for the two substances were less than 2.0%; and the recovery values for pseudoepherine hydrochloride and triprolidine hydrochloride were 99.98 + 1.05% and 99.73 + 1,54% respectively. The result showed that the samples analysed contained pseudoephedrine hydrochloride 94.36% of the labeled ammount, and triprolidine hydrochloride 94.44% of the la-beled ammount.